2013
DOI: 10.1002/hbm.22304
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal insulin increases regional cerebral blood flow in the insular cortex in men independently of cortisol manipulation

Abstract: Insulin and cortisol play a key role in the regulation of energy homeostasis, appetite, and satiety. Little is known about the action and interaction of both hormones in brain structures controlling food intake and the processing of neurovisceral signals from the gastrointestinal tract. In this study, we assessed the impact of single and combined application of insulin and cortisol on resting regional cerebral blood flow (rCBF) in the insular cortex. After standardized periods of food restriction, 48 male volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 74 publications
(112 reference statements)
7
76
2
1
Order By: Relevance
“…Acute and chronic intranasal insulin administration improved memory and other cognitive functions in healthy adults with obesity or T2DM 114123 , and neuroimaging studies found that intranasal insulin alters activation of cognitive brain regions and resting-state connectivity between the hippo campal region and the default-mode network 124126 . Electrophysiology studies, including measurement of event-related potentials 127 , direct-current brain potentials 128 and magnetoencephalography 129,130 , also detected changes in response to acute intranasal insulin administration in healthy individuals and in people with obesity.…”
Section: Insulin and The Brainmentioning
confidence: 99%
“…Acute and chronic intranasal insulin administration improved memory and other cognitive functions in healthy adults with obesity or T2DM 114123 , and neuroimaging studies found that intranasal insulin alters activation of cognitive brain regions and resting-state connectivity between the hippo campal region and the default-mode network 124126 . Electrophysiology studies, including measurement of event-related potentials 127 , direct-current brain potentials 128 and magnetoencephalography 129,130 , also detected changes in response to acute intranasal insulin administration in healthy individuals and in people with obesity.…”
Section: Insulin and The Brainmentioning
confidence: 99%
“…It is therefore important to characterize the specific dimensions of fatigue that develop in patient populations, and assess the role of inflammation. For instance, some aspects of fatigue may be derived from sleep alterations or changes in hormonal regulation in clinical populations, e.g., of insulin or cortisol, which can modulate brain functions including those in the above-mentioned areas (138140). …”
Section: Potential Neuronal Mechanisms Underlying Dimensions Of Inflamentioning
confidence: 99%
“…Recently, one group measured brain activity using positron emission tomography and found higher 18 F fluorodeoxyglucose uptake in the parietotemporal, frontal, precuneus and cuneus regions of the brain in patients receiving intranasal delivery of insulin [57]; however, the sample size was relatively small [58]. A recent systematic review [59] summarized that the underlying mechanism for intranasal delivery of insulin treating AD may be that this form of delivery could reverse brain atrophy, and bilateral, locally distinct regional cerebral blood flow (rCBF) was increased after insulin administration in the insular cortex and the putamen [59,60]. In addition, the neuroenergetic level was enhanced by intranasal insulin [61], and in turn, intrinsic brain activity was also increased in the hypothalamus and orbitofrontal cortex [62].…”
Section: Insulinmentioning
confidence: 99%